Sheep and goats, men and women: Household relations and small ruminant development in southwest Nigeria - Okali, C.; Sumberg, J.E. (Elsevier, 1985)
Describes small ruminant production systems for the humid areas of southern Nigeria. Discusses the differences in ownership patterns between men and women; household relations particularly decision making processes related to the potential use of browse as fertilizer or feed; and the unique nature of small ruminants among agricultural resources.